Evaluating the Efficacy of Ayurvedic Treatments in Stage V Chronic Kidney Disease: A Case Report (Advances in Applied Biological Research, 2024)
Chronic Kidney Disease,  Ayurveda, Mutraaghaata symptoms significantly improved.  The patient’s key laboratory parameters, such as serum creatinine, urea, and serum  uric acid, also showed marked improvement, trending toward normal levels at the  time of discharge. The treatment regimen included Ayurvedic oral medications  like Tab. Asthipurak, Tab. Chander Vati, Renal Support syrup, and GFR powder,  complemented by Panchakarma procedures such as Awgaha Swedan, Matra Basti,  Kashaya Basti, and Shiroabhyanga. The results of this case indicate that Ayurvedic interventions can lead to significant  improvements in both biochemical markers and clinical symptoms in patients  with Stage V CKD. These findings suggest that Ayurveda may offer a promising  complementary or alternative approach to conventional CKD treatment,  highlighting the need for further research in this area
Keywords: Chronic Kidney Disease; Ayurveda; Mutraaghaata